2020
DOI: 10.3389/fimmu.2020.00812
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Natural Killer Cell Homeostasis

Abstract: Natural killer (NK) cells have a central role within the innate immune system, eliminating virally infected, foreign and transformed cells through their natural cytotoxic capacity. Release of their cytotoxic granules is tightly controlled through the balance of a large repertoire of inhibitory and activating receptors, and it is the unique combination of these receptors expressed by individual cells that confers immense diversity both in phenotype and functionality. The diverse, yet unique, NK cell repertoire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 153 publications
(185 reference statements)
1
37
0
Order By: Relevance
“…Finally, the confinement model was also proposed, taking into account the adhesion molecules (He and Tian 2017). More recently, from a mechanistic point of view, the presence of dense-core secretory lysosomes containing the cytolytic effector protein granzyme B distinguishes educated from uneducated resting NK cells (Goodridge et al 2019, Pfefferle et al 2020). Kim et al have revealed that the IR from the Ly49 family can efficiently license NK cells (Kim et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the confinement model was also proposed, taking into account the adhesion molecules (He and Tian 2017). More recently, from a mechanistic point of view, the presence of dense-core secretory lysosomes containing the cytolytic effector protein granzyme B distinguishes educated from uneducated resting NK cells (Goodridge et al 2019, Pfefferle et al 2020). Kim et al have revealed that the IR from the Ly49 family can efficiently license NK cells (Kim et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, cells that acquired phenotypes of the greatest proliferative potential were least cytotoxic and most prone to apoptosis. Understanding the impact of such finely balanced homeostatic mechanisms in the artificial environment of ex vivo NK cell expansion may ultimately redefine an "ideal" donor and expanded cell composition [41]. "Adaptive" or "memory-like" NK cells are a subset of therapeutic interest because of their improved survival and cytolytic capabilities [42].…”
Section: Starting Materials: Sources Of Nk Cells For Therapeutic Usementioning
confidence: 99%
“…NK cells are unique lymphocytes that can recognize and kill aberrant cells without antibodies or major histocompatibility complex (MHC) [ 48 ]. Therefore, NK cells are key for tumor cell surveillance, because tumor cells that are missing MHC I markers cannot be detected and destroyed by other immune cells, such as T-cells [ 49 ]. Although NK cells lack antigen-specific cell surface receptors, they have many alternative receptors that can recognize tumor cells, including NKG2D, NKp44, NKp46, NKp30, and DNAM [ 50 , 51 ].…”
Section: Immunocyte Membrane Molecules Contributing To Nanomateriamentioning
confidence: 99%